2016
DOI: 10.1371/journal.pone.0159140
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis and Systematic Review on the Association between Human Papillomavirus (Types 16 and 18) Infection and Esophageal Cancer Worldwide

Abstract: BackgroundEsophageal cancer is a common and aggressive malignant tumor. This study aimed to investigate the association between human papillomavirus (HPV) Types 16 and 18 and esophageal carcinoma (EC) in the world population by conducting a meta-analysis.Materials and MethodsComputerized bibliographic and manual searches were performed to identify all eligible literatures between 1982 and 2014. PUBMED (http://www.ncbi.nlm.nih.gov/pubmed/) and CNKI (http://www.cnki.net/) were the primary sources of case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
2
24
0
1
Order By: Relevance
“…A recent systematic review of the relationship between HPV infection (types 16 and 18) and esophageal cancer worldwide found that HPV is closely associated with esophageal cancer in China, and in other countries, with an integrated OR=1.62 (95% CI: 1.33–1.98) 42 . The highest HPV prevalence was found in Africa and Asia; notably, this result was obtained among Chinese studies from provinces with high ESCC incidence rates 43 .…”
Section: Risk Factors Of Esccmentioning
confidence: 99%
“…A recent systematic review of the relationship between HPV infection (types 16 and 18) and esophageal cancer worldwide found that HPV is closely associated with esophageal cancer in China, and in other countries, with an integrated OR=1.62 (95% CI: 1.33–1.98) 42 . The highest HPV prevalence was found in Africa and Asia; notably, this result was obtained among Chinese studies from provinces with high ESCC incidence rates 43 .…”
Section: Risk Factors Of Esccmentioning
confidence: 99%
“…Some of the HPV types detected in our analysis coincide with that reported in our previous study, also using the Luminex technique 34 . These types identi ed with low frequency are little studied in the literature 49 .…”
Section: Discussionmentioning
confidence: 99%
“…В научной литературе хорошо известны случаи возникновения рака щитовидной железы спустя годы после лучевого воздействия [9]. Предположительно, персистенция вируса папилломы человека вызвала процесс малигнизации в пищеводе, что является одним из доказанных факторов риска [10].…”
Section: Discussionunclassified